Anchoring educational leadership on culture and spirituality in Chinese-Filipino Christian Schools - Dy, Chui Eng Tan (Animo Repository, 2015)
[Anchoring Educational Leadership on Culture and Spirituality: A Case Study on Educational Leadership in Chinese-Filipino Christian Schools was undertaken to discover and develop a model of educational leadership among successful Chinese- Filipino Christian School leaders. Four Leaders and their schools representing Luzon, Visayas and Mindanao were the participants of the study. The research questions asked were: How may the organizational culture of the Chinese-Filipino Christian schools be described and why? How do the school organizational culture and societal cultural forces influence leadership in the Chinese-Filipino Christian School?What are the essential characteristics of leadership, management and decision processes in the Chinese-Filipino Christian schools? Why are the distinctive characteristics of leadership, management and decision processes essential in the Chinese-Filipino Christian schools? What leadership model may emerge from the analysis of leadership in the Chinese-Filipino Christian schools? Storytelling, in-depth interviews, and observation through onsite immersion were the employed data gathering techniques. The inclusion criteria were: the school headed is basic education its good performance is based on external national recognition such as voluntary accreditation status the leader must have spent at least five years as head of that school She/he is identified as effective by external peers and she/he has willingness to participate in the study. The analysis followed several steps including coding (Yin, 2009), open coding and axial coding (Corbin & Strauss, 2008), identification of lower categories, and move on to higher categories level, representing more abstract concept (Yin 2011). A further step was done to explore the dimensions using Corbin and Strauss that included context or what it is about -- Chinese Filipino Christian Leadership the causal condition or what move them to leadership position the nature of Phenomenon or what is natural to their living the inter action / strategy or activities done in the school and finally the outcome or result of the leadership. The result of the study generated a leadership framework for Chinese-Filipino Christian Schools and drew out the following conclusions: 1. The Chinese-Filipino Christian leadership is strongly adhered to Christian Spirituality 2. The leaders conduct school management by emphasizing a culture of industriousness, discipline, diligence, mutual support, and caring, creating a family like environment 3. They face many challenges relating to how to preserve Filipino-Chinese Christian culture, yet they remain successful in surpassing the regulation requirements and quality standards and that 4. These school leaders are driven more by spirituality than by their cultural strengths. They have drawn heavily on the positive traits of their cultural and spiritual heritage.